“Tahukah kamu?”: Analisis Set Data Survei Sosial Ekonomi Nasional (Susenas) - Johar, Meliyanni; Soewondo, Prastuti; Pujisubekti, Retno; Satrio, Harsa Kunthara; Adji, Ardi; Wibisono, Iqbal Dawam (UI Scholars Hub, 2019)
Susenas has been the backbone of many scientific research and public policies in Indonesia since 1960s. Nonetheless, some of its features have not been clearly conveyed and understood. We highlight two features that often lead to misinterpretation. First, the expenditure variable in Susenas does not measure private outlay but household’s consumption because it includes external assistance. Incomes of households which receive many assistances therefore are overestimated. Second, a sudden change in questionnaire since 2015 may disrupt trend analysis. Specifically for health items, this abrupt change coincides with any change stimulated by a new health initiative introduced by the Central Government.